The use of turn taking in the 2020 US presidential debate: A conversation analysis study - Aryanti, Maya Lisa; Yuliawati, Susi; Ekawati, Dian; Darmayanti, Nani (Universitas Mulawarman, 2024)
The 2020 US presidential debate was a democratic practice held every four years. In the debate, each debater used turn taking strategies. This research focuses on the uses of turn taking strategies and their types dominantly produced by the debaters in the debate. The strategies encompass taking, holding, and yielding the turn. Elaborating the strategy in depth is the aim of this research. Qualitative conversation analysis technique using turn-by-turn consideration was the used method. The utterances of the debaters were the data. The data source was a self-made transcription based on the video recording of the debate. Overlapping, interruption, repair, and other debater selection often occur in the debate through those strategies. Consequently, TRP frequently cannot be reached, and the usage of these strategies affects turn allocation. The results show that turn taking strategies were applied in the debate. Trump used taking the turn and yielding the turn as strategies. Meanwhile, Biden used holding the turn as his strategy. For future research, discussions on turn-taking subcategories in the scope of political debates and conversation analysis are expected to be conducted more.